Ice Scours in the Sediments of Glacial Lake Iroquois, Prince Edward County, Eastern Ontario - Gilbert, Robert; Handford, Karen; Shaw, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1992)
ABSTRACTStraight or slightly curved ice scours are found in thin glacilacustrine sediment of eastern Lake Iroquois, especially near the crest of an escarpment in Prince Edward County. They are large (to 3.57 km long and 174 m wide), shallow (about 1 m deep) and oriented in a nearly westerly direction. Irregular ridges of sediment have been pushed up along the sides and at the western end of some scours. Bedrock is near the ground surface, but had little influence on the formation of the scours. Based on their shape, location and pattern, we conclude that the scours were most likely formed in shallow water of the short-lived Sydney phase of Lake Iroquois by lake ice driven by prevailing northeasterly winds from the retreating Laurentide Ice Sheet.